On the formation and role of reactive oxygen species in light-driven LPMO oxidation of phosphoric acid swollen cellulose. (7th August 2017) - Möllers, K.B.; Mikkelsen, H.; Simonsen, T.I.; Cannella, D.; Johansen, K.S.; Bjerrum, M.J.; Felby, C.
Abstract: Light-driven activation of lytic polysaccharide monooxygenases (LPMOs) has been attributed to the transfer of high redox potential electrons from excited photopigments to the enzyme. However, due to the formation of reactive oxygen species (ROS) in such a system, not only electrons from the pigments but also ROS could be part of the enzyme mechanism. This work investigates the role of ROS in the oxidation of phosphoric acid swollen cellulose (PASC) by a light-driven LPMO system. Our results clearly show that the addition of superoxide dismutase or catalase to remove ROS did not attenuate the capacity of the light-driven LPMO system to oxidize PASC, as measured by formation of oxidized oligosaccharides. We conclude that ROS are not part of the light-driven LPMO activation; hence, transfer of high redox potential electrons from the excited photopigment to the LPMO remains the most likely mechanism under the conditions tested in this study. Graphical abstract: Highlights: The formation of superoxide and hydrogen peroxide by light-excited chlorophyllin was detected. Removal of ROS by superoxide dismutase or catalase did not attenuate the light-driven LPMO oxidation of cellulose. Transfer of electrons from the excited photopigment to the LPMO is a likely mechanism for light-driven activation of LPMOs.